The sum of all kisses - Quinn, Julia, 1970- (New York, New York; Avon, 2013)
When they have to spend a week together, the antagonism between Hugh Prentice, a crippled, bookish mathematician, and Lady Sarah Pleinsworth, who blames him for the duel that forced her cousin into exile, turns to something more.
Keywords: Man-woman relationships -- Fiction; Mathematicians -- Fiction; Nobility -- England -- Fiction; Historical fiction; Love stories